Dataset: Multi-view video sequences of Megathyrsus maximus in greenhouse conditions for 3D reconstruction and temporal phenotyping - Ruiz-Hurtado, Andres Felipe; Arrechea-Castillo, Darwin Alexis; Mayorga Cobos, Mildred Julieth; Madera Doria, Yaira Yulieth; Escobar Graciano, Miller; Cardoso Arango, Juan Andres (2025)
This dataset contains 80 4k videos of 20 individual Megathyrsus maximus plants. Each plant was recorded at four distinct developmental stages for 4 weeks under greenhouse conditions. The dataset is intended as a primary source for 3D reconstruction using Neural Radiance Fields (NeRF) and 3D Gaussian Splatting (3DGS).